COMPETITIVE STRATEGY OF A MARKET LEADER; CASE OF UD. PRIMADONA’S PROL TAPE JEMBER - EAST JAVA - Adetiya Prananda Putra; Idqan Fahmi; Yossi Wibisono (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The purpose of this study was to formulate a competitive strategy to maintain the existence of Prol Tape Primadona. The study used a case study approach with UD. Primadona as the research object. The data were analyzed by using a value chain approach to determine the internal and external conditions that influence Prol Tape Primadona and using analysis of IFE, EFE, CPM, IE, SWOT, and QSPM to develop competitive strategies for Prol Tape Primadona. The results show that the strategies that can be recommended to UD. Primadona are as follows: 1) increasing production capacity, 2) creating website/blog to promote Prol Tape, 3) adding the variants of Prol Tape, 4) stricting quality control to maintain strong brand equity, and 5) establishing coordination with the district government of Jember to make Prol Tape as a superior product.Keywords: competitive strategy, Prol Tape Primadona, UD. Primadona, QSPM, SWOTAbstrakPenelitian ini bertujuan untuk merumuskan strategi bersaing sehingga dapat menjaga eksistensi Prol Tape Primadona. Penelitian menggunakan pendekatan studi kasus dengan UD. Primadona sebagai objek penelitiannya. Data dianalisis dengan pendekatan rantai nilai untuk mengetahui kondisi internal dan eksternal yang berpengaruh terhadap prol tape Primadona kemudian menggunakan analisis IFE, EFE, CPM, IE, SWOT, dan QSPM untuk menyusun strategi bersaing Prol Tape Primadona. Hasil penelitian menunjukkan bahwa strategi-straegi prioritas yang dapat direkomendasikan kepada UD. Primadona yaitu 1) peningkatan kapasitas produksi, 2) membuat situs web/blog untuk mempromosikan Prol Tape, 3) melakukan penambahan varian Prol Tape, 4) pengendalian  mutu yang ketat untuk menjaga ekuitas merek yang kuat, dan 5) melakukan koordinasi dengan pemerintah kabupaten Jember untuk menjadikan Prol Tape sebagai salah satu produk unggulan.Kata kunci: strategi bersaing, Prol Tape Primadona, UD. Primadona, QSPM, SWOT